A new fossil species of Largusoperla (Plecoptera: Perlidae) and its evolutionary implications - Chen, Zhi-Teng (Zootaxa, 2018)
A new species of the fossil stonefly genus Largusoperla Chen, Wang & Du, Largusoperla difformitatem sp. nov. is reported new to science from mid-Cretaceous Burmese amber. The morphological characters of the new species are described, illustrated, and compared to other known species of the genus. The unique morphological characters of Largusoperla, including the asymmetrical paraprocts of L. difformitatem sp. nov. are discussed from a possible evolutionary perspective.